Proses Belajar dalam Rangka Pewarisan Calempong Oguang Sialang Kecamatan Kapur IX Kabupaten Lima Puluh Kota - Pano Pio Putra; Marzam Marzam (SENDRATASIK UNP, 2022)
The type of research conducted is qualitative research with descriptive methods. The types of data used in this study are in the form of primary data and secondary data, and make the researcher the main instrument of research assisted by supporting instruments such as; stationery, photo camera and digital camera. Data collection techniques were carried out through observation, interviews, documentation and literature studies. The steps in analyzing the data are done by reducing the data, presenting the data, drawing conclusions and verifying the data. The results showed that the effort to inherit the art of Calempong Oguang Sialang was an open system involving the government participating in maintaining and teaching it to the younger generation. The stages of teaching carried out include; 1) the implementation of prayer; 2) introduction to the tools used; 3) song introduction; 4) the appearance of Calempong Oguang Sialang by the eldest, and; 5) Individuals are taught one by one different musical instruments. The efforts that have been made have been welcomed by the whole community. Because according to them Calempong Oguang Sialang must be preserved so that it doesn't become extinct and just abandoned.